An autonomous robotic system to maintain free flowing drains - Costa, Joy; Chowdhury, Md. Sayeem; Inam, Istiak Ahmed (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.